Legitimacy and Public Trust in Coalition Governments: A Malaysian Perspective - Pandian, Sivamurugan; Sulaiman, Aizatie Najmin (Asian Social Work Journal, 2025)
This article examines the issue of legitimacy in coalition governments in Malaysia following the 15th General Election (GE15), which for the first time produced a hung parliament and subsequently a unity government. While constitutionally valid through parliamentary majority support and the consent of the Yang di-Pertuan Agong, public acceptance of this government remains fragile. Adopting a qualitative approach, the study draws on 31 informants through in-depth interviews (IDI) and focus group discussions (FGD), complemented by secondary document analysis. The findings highlight five major themes undermining popular legitimacy: perceptions of a “forced coalition,” concerns about party dominance, the persistence of identity politics based on race and religion, unclear and inconsistent policy communication and economic confidence. These results are interpreted using Easton’s theory of specific versus diffuse support, Schmidt’s framework of input, output and throughput legitimacy and Public Choice Theory (Buchanan & Tullock). The study also underscores the Sarawak GPS model as an alternative example of coalition stability, achieved through a collective identity, ethnic consensus, and development-oriented politics. Overall, the article contributes to the literature by emphasizing that the legitimacy of coalition politics does not rest solely on parliamentary numbers, but also on the government’s ability to rebuild public trust through transparent communication, balanced power-sharing, and inclusive policymaking.